The city of the inhabitants and their wishes: The city of the inhabitants and their wishes - García Moreno, Beatriz (Corporación Universitaria del Caribe, CECAR., 2019)
It is said that in the transformations of the city not only the institutions and their planning agencies intervene, but the practices of their inhabitants, considered these as speaking beings provided with desire and enjoyment. Through these practices, space, when appropriate, becomes a place; the built city becomes malleable; its forms, apparently predefined, are offered for contingent and multiple uses; and that the different temporalities that constitute it, are updated in a present. The inhabitants-subjects, for their practices, require a symbolic field that provides channels for their desire to flow.Keywords: City, Subjects, Desire, Enjoyment.